1997
DOI: 10.1128/aac.41.2.419
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of multiple phases of human immunodeficiency virus type 1 replication by a dithiane compound that attacks the conserved zinc fingers of retroviral nucleocapsid proteins

Abstract: The human immunodeficiency virus type 1 (HIV-1) nucleocapsid p7 protein contains two retrovirus-type zinc finger domains that are required for multiple phases of viral replication. Chelating residues (three Cys residues and one His residue) of the domains are absolutely conserved among all strains of HIV-1 and other retroviruses, and mutations in these residues in noninfectious virions. These properties establish the zinc finger domains as logical targets for antiviral chemotherapy. Selected dithiobis benzamid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
70
0

Year Published

1998
1998
2014
2014

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(73 citation statements)
references
References 48 publications
3
70
0
Order By: Relevance
“…Because of the critical role of the cysteines in the zinc fingers, covalent binding zinc ejectors are not susceptible to the development of resistance (Jenkins et al, 2010). Various categories of compounds in this class were reported during the 1990s, including 3-nitrosobenzamide (NOBA) (Rice et al, 1993), 2,2’-dithiobisbenzamide (DIBA) (Rice et al, 1995), cyclic 2,2’- dithiobisbenzamide (Witvrouw et al, 1997), 1,2-dithiane-4,5-diol-1,1-dioxide (Rice et al, 1997a), azadicarbonamide (ADA) (Rice et al, 1997b) and pyridinioalkanoyl 2-mercaptobenzamide thioesters (PATE) (Turpin et al, 1999). The structure and activity of these zinc ejectors has been reviewed by Rocquigny et al (de Rocquigny et al, 2008).…”
Section: Zinc Finger Bindersmentioning
confidence: 99%
“…Because of the critical role of the cysteines in the zinc fingers, covalent binding zinc ejectors are not susceptible to the development of resistance (Jenkins et al, 2010). Various categories of compounds in this class were reported during the 1990s, including 3-nitrosobenzamide (NOBA) (Rice et al, 1993), 2,2’-dithiobisbenzamide (DIBA) (Rice et al, 1995), cyclic 2,2’- dithiobisbenzamide (Witvrouw et al, 1997), 1,2-dithiane-4,5-diol-1,1-dioxide (Rice et al, 1997a), azadicarbonamide (ADA) (Rice et al, 1997b) and pyridinioalkanoyl 2-mercaptobenzamide thioesters (PATE) (Turpin et al, 1999). The structure and activity of these zinc ejectors has been reviewed by Rocquigny et al (de Rocquigny et al, 2008).…”
Section: Zinc Finger Bindersmentioning
confidence: 99%
“…54 Another compound, NSC 624151 was found to be active against wild type and drug resistant HIV-1 and HIV-2 viruses. 55 A third compound e Azodicarbonamide, when introduced in phase I and II trials in Europe for advanced AIDS, showed dose dependent side effects (nephrolithiasis, glucose intolerance, CD4 cytotoxicity). 56 The side effects are not unsurprising as zinc fingers are not unique targets or used by HIV alone and are found in mammalian cells.…”
Section: Novel Targets and Agents Undergoing Pre-clinical Or Early CLmentioning
confidence: 99%
“…The non-dissociable tethered dithiane compound 1,2-dithiane-4,5-diol,1,1-dioxide, (NSC 624151) also mediates similar defects in Gag processing (Rice et al 1997). Although cellular proteins also contain zinc fingers, these inhibitors appear to preferentially target retro-viral zinc fingers.…”
Section: Targeting Hiv-1 Ncmentioning
confidence: 99%